Elements of healthcare delivery required to facilitate the clinical governance of hospital pharmacy services: a document review - Huri Balikubiri; Anna Kemp-Casey; Andre Q. Andrade; Elizabeth E. Roughead (Health Research Policy and Systems)
Abstract Background Clinical governance of hospital pharmacy services aims to ensure the delivery of pharmaceutical care that maximizes positive outcomes for patients. Good clinical governance incorporates service-related data to evaluate and improve care delivery. National-level clinical governance frameworks available in Australia provide limited information on auditable metrics to evaluate hospital pharmacy services. This study reviews healthcare governance documents to determine the goals and desirable elements of healthcare delivery and the information to measure to inform the clinical governance of hospital pharmacy services. Methods A purposive online search was conducted to identify healthcare governance documents describing the clinical governance approach for general healthcare and hospital pharmacy services in Australia, New Zealand, England, Canada and the United States. Documents for general healthcare settings were reviewed to identify the goals and desirable elements of healthcare delivery. Pharmacy governance documents were then reviewed to contextualize the identified elements of care to hospital pharmacy services and to determine the information to measure to inform clinical governance. Results The objective of delivering quality healthcare was included in all documents. Quality healthcare was described in the documents as healthcare that is patient-centred, safe, effective, integrated, timely, equitable, efficient and reliable. These factors were considered desirable elements of healthcare delivery that promote positive patient outcomes. The performance measures to evaluate and improve hospital pharmacy services delivery covered pharmacists’ clinical activities, pharmaceutical care outcomes, stakeholder feedback and medication incidents and risks. Conclusions Measuring the extent to which the desirable elements of care are evident in the performance of clinical pharmacists’ activities and the associated outcomes of care may provide useful information to facilitate the clinical governance of hospital pharmacy services.